Effect of chronic femoral artery ligation on skeletal muscle interstitial prostaglandin E₂ concentration in the rat: implications for mechanoreflex sensitization - Felice, Kennedy (Kansas State University, 2019)
Autonomic adjustments during exercise include a withdrawal of parasympathetic stimulation of the heart and an increase in the sympathetic stimulation of the heart and other organs/vascular beds. These adjustments are mediated, in part, by the exercise pressor reflex, a neural feedback mechanism activated by stimulation of group III and group IV afferents whose sensory endings are located within contracting skeletal muscle. Group III (mechanoreflex) and group IV (metaboreflex) afferents are primarily mechanically and metabolically sensitive, respectively. Cyclooxygenase (COX) products within skeletal muscles have the potential to sensitize the mechanical component of the exercise pressor reflex (i.e., mechanoreflex) in a variety of clinical populations including peripheral artery disease patients. For example, we found recently that COX inhibition reduced the pressor response evoked during hindlimb muscle stretch, a model of isolated mechanoreflex activation, in rats in which a femoral artery was ligated ~72 hours before the experiment (a model of simulated PAD in the rat). Conversely, we found no effect of COX inhibition on the mechanoreflex in normal, control rats. To investigate a potential mechanism of COX-mediated mechanoreflex sensitization in rats with ligated femoral arteries, we used the muscle microdialysis technique to test the hypothesis that femoral artery ligation in the rat increased resting skeletal muscle interstitial concentrations of the COX-metabolite prostaglandin E₂ (PGE₂). Contrary to our hypothesis, in 12 rats we found no difference in resting PGE₂ between control (i.e., freely perfused, 196±33 pg/ml) and the contralateral ligated (236±43 pg/ml, p=0.15) hindlimb. Moreover, we found that hindlimb muscle stretch increased PGE₂ concentration in freely perfused skeletal muscles (Δ PGE₂: 55±22 pg/ml, p=0.05) but not ligated (Δ PGE₂: 19±20 pg/ml, p=0.98) skeletal muscles. Collectively, the present results suggest that COX-mediated mechanoreflex sensitization in the ligated rat model of simulated PAD is not attributable to elevated resting COX-metabolite levels or an exaggerated increase in COX-metabolite concentration during isolated mechanoreflex activation.
Keywords: Pressor; Reflex; COX Metabolites